Challenges and Implementation of Disability Rights in Singaraja Correctional Facility: A Study of Article 37 of Law No. 8/2016 - Sariasa, Gede; Yuliartini, Ni Putu Rai; Mangku, Dewa gede Sudika (Universitas Internasional Batam, 2024)
This research discusses the implementation of Article 37 Paragraph (1) of Law Number 8 of 2016 concerning Persons with Disabilities at the Class IIB Singaraja Correctional institution. The objectives of this study are to: (1) Understand and analyze the implementation of Article 37 Paragraph (1) of Law Number 8 of 2016 concerning Persons with Disabilities at the Class IIB Singaraja Correctional Facility, and (2) Identify and analyze the obstacles to implementing Article 37 Paragraph (1) of Law Number 8 of 2016 concerning Persons with Disabilities at the Class IIB Singaraja Correctional Facility. This research is an empirical legal research that is descriptive in nature. The findings of the study are: (1) The implementation of Article 37 Paragraph (1) of Law Number 8 of 2016 concerning Persons with Disabilities at the Class IIB Singaraja Correctional Facility has been pursued to the best extent possible through the establishment of a Disability Service Unit and the fulfillment of various rights and supporting facilities. However, many of the supporting facilities provided do not yet meet the standards mandated by the law. (2) The factors hindering the implementation of Article 37 Paragraph (1) of Law Number 8 of 2016 concerning Persons with Disabilities at the Class IIB Singaraja Correctional institution include limited land, lack of human resources such as the shortage of trained staff to handle disabled inmates, budget constraints, and the ongoing issue of overcrowding at the Class IIB Singaraja Correctional institution.